2020
DOI: 10.1002/mp.14589
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative positron emission tomography imaging in the presence of iodinated contrast media using electron density quantifications from dual‐energy computed tomography

Abstract: Purpose As preparation for future positron emission tomography (PET)/dual‐energy computed tomography (DECT)T imaging modality and new possible clinical applications, the study aimed to evaluate the utility of clinically available spectral results from a DECT system for improving attenuation corrections of PET acquisitions in the presence of iodinated contrast media. The dependence of the accuracy of PET quantification values, reconstructed with conventional and spectral‐based attenuation corrections, was exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…31 However, changes in Hounsfield units due to iodinated contrast in PET/CT leads to an overestimation of attenuation by the CT attenuation correction leading to elevated SUV. [31][32][33] The results of this study demonstrated that SUV mean and SUV max were not affected by the injection of a GBCA during simultaneous breast PET/MR imaging. The attenuation of annihilation photons caused by the presence of the GBCA is likely not substantial enough to cause a significant difference in detected signal.…”
Section: F I G U R Ementioning
confidence: 79%
See 1 more Smart Citation
“…31 However, changes in Hounsfield units due to iodinated contrast in PET/CT leads to an overestimation of attenuation by the CT attenuation correction leading to elevated SUV. [31][32][33] The results of this study demonstrated that SUV mean and SUV max were not affected by the injection of a GBCA during simultaneous breast PET/MR imaging. The attenuation of annihilation photons caused by the presence of the GBCA is likely not substantial enough to cause a significant difference in detected signal.…”
Section: F I G U R Ementioning
confidence: 79%
“…There does not appear to be significant attenuation of annihilation photons by iodine contrast agents at 511 keV in general use cases 31 . However, changes in Hounsfield units due to iodinated contrast in PET/CT leads to an overestimation of attenuation by the CT attenuation correction leading to elevated SUV 31–33 …”
Section: Discussionmentioning
confidence: 99%
“…An in‐house software tool 28 , 30 , 31 , 32 was used to automatically place the regions of interest (ROI) on each insert (covering 60% of the insert diameter, that is 17 mm) for MonoE 70 keV images of both insert configurations and phantom size combinations obtained with a DRI of 23. These ROI placements were then copied to corresponding locations on other spectral results to measure the mean and standard deviation of voxel values.…”
Section: Methodsmentioning
confidence: 99%
“…An in-house software tool 28,[30][31][32] Values that fell within the expected range of values was considered accurate. These results were illustrated by plotting the CT number for each insert versus keV with an envelope that represents the range of expected values.…”
Section: Image Analysismentioning
confidence: 99%